Autorotation: Is there a live man's curve? - Silva Scarpari, J.R.; De Andrade, D. (My University, 2014)
The autorotation flight of single engine helicopters has peculiarities in terms of performance and flying qualities. This research discusses these specific characteristics from the perspective of certification processes, especially based on the FAR-27, focusing on human factors of flight safety. It describes the factors that decisively influence the workload of the pilot during an engine failure and the actions necessary to perform a safe landing in autorotation. These factors are related to natural and artificial alarms, aerodynamic imbalances, especially in the moments following the engine failure; the reaction time of the pilot and the correct lowering collective control rate. The methodology to determine the unsafe areas of the height-speed diagram, the "dead man's curve", is investigated, quantified and compared with the main international standards and validated on a flight-test campaign, performed on an aircraft (AS-350) of the Brazilian Air Force, carried out by test pilots and engineers with the Test Flight and Research Institute (IPEV). Such studies suggest a methodology to define the risk level curve instead of the dead man’s curve in order to reduce the catastrophic damages resulting from inadequate interpretations of the pilots during full autorotation flight, as well as to advise the authorities involved in the process of certification of these types of helicopters.